Development and evaluation of a modular smoke evacuator for surgical smoke control - Suksan Kanoksin; Suphakarn Techapongsatorn (PLoS ONE, 2026)
Background Surgical smoke generated during energy-based operations is a known hazard containing particulate matter (PM), volatile organic compounds (VOCs), and biological debris, with insufficient adoption of commercial smoke evacuators due to cost and complexity. Objective This study aimed to develop a cost-effective, modular and passive smoke evacuator and evaluate its efficacy in reducing PM and VOC levels during simulated laparoscopic procedures. Methods A prototype smoke evacuator incorporating a distilled water bubbling trap, activated carbon filter, and ULPA filter was tested in a sealed chamber simulating laparoscopic surgery using porcine liver tissue. The system was connected to a laparoscopic port through a three-way valve, allowing manual, on-demand smoke evacuation without continuous suction. Air quality metrics, including PM 1.0 , PM 2.5 , PM 10 , VOC, and CO₂, were measured continuously. Results were compared to baseline and performance benchmarks from commercial smoke evacuation systems. Statistical analysis was performed using paired t-tests. Results The prototype evacuator reduced PM 2.5 levels by >99.5% and VOC concentrations by >95% compared to no-evacuation control trials (p < 0.01). CO₂ concentrations returned to baseline following evacuation, indicating minimal disturbance of chamber atmosphere. PM 2.5 and VOC levels were restored to near-baseline values. Conclusion The developed modular passive smoke evacuator offers a promising and cost-effective solution to improve air quality and enhance occupational safety in operating rooms. The model represents an idealized simulation of laparoscopic smoke evacuation; further clinical validation in live surgical environments is warranted.